Engineering design planning and management - Jack, Hugh (Academic Press/Elsevier, 2013)
Engineering Design, Planning and Management covers engineering design methodology with an interdisciplinary approach, concise discussions, and a visual format. The book covers the product design process in the context of both established companies and entrepreneurial start-ups. Readers will discover the usefulness of the design process model through practical examples and applications from across the engineering disciplines. Author Hugh Jack takes the reader through phases ranging from risk assessment and need identification through specification and detailed design, addressing intellectual property issues as well. Recognizing that design is a process commonly performed in teams, Jack also covers project management and team dynamic topics where appropriate.